Pengembangan Penerapan Augmented Reality untuk Informasi Fasilitas Kampus - Latifah, Ayu; Rahayu, Raden Erwin Gunadhi; W, Shantang Adhiimusyari (Institut Teknologi Garut, 2024)
The application of sophisticated Augmented Reality (AR) technology in providing information about campus facilities is an innovative and effective approach. Continuous research is developing an Augmented Reality application that will provide a visual display of the facilities on the Garut Institute of Technology campus. This research effort is to change the Augmented Reality approach which previously focused on layout displays to place more emphasis on virtual displays of facilities, so that they are easier for students to understand. The research method used is Research and Development (RnD) carried out using the ADDIE development approach, which involves the sequence analyze, design, develop, implement and evaluate. Application development is carried out using Visual Studio Code software. The results of this research show a virtual visualization of campus facilities, including various areas such as classrooms, parking areas, canteens, prayer rooms, and language laboratories. Users can access visualizations of these facilities via smartphones and other hardware, allowing them to view these facilities in virtual form and with detailed depictions of campus facilities. The results of testing user satisfaction with the application show a very good level of acceptance.